Adaptive servoventilation in clinical practice: beyond SERVE-HF?. Issue 4 (23rd October 2017) - Randerath, Winfried; Schumann, Katja; Treml, Marcel; Herkenrath, Simon; Castrogiovanni, Alessandra; Javaheri, Shahrokh; Khayat, Rami
Adaptive servoventilation (ASV) has proven effective at suppressing breathing disturbances during sleep, improving quality of life and cardiac surrogate parameters. Since the publication of the SERVE-HF-trial, ASV became restricted. The purpose of this study was to evaluate the clinical relevance of the SERVE-HF inclusion criteria in real life and estimate the portion of patients with these criteria with or without risk factors who are undergoing ASV treatment. We performed a retrospective study of all patients who were treated with ASV in a university-affiliated sleep laboratory. We reviewed the history of cardiovascular diseases, echocardiographic measurements of left ventricular ejection fraction (LVEF) and polysomnography. From 1998 to 2015, 293 patients received ASV, of which 255 (87.0%) had cardiovascular diseases and 118 (40.3%) had HF. Among those with HF, the LVEF was ≤45% in 47 patients (16.0%). Only 12 patients (4.1%) had LVEF <30%. The SERVE-HF inclusion criteria were present in 28 (9.6%) ASV recipients. Of these patients, 3 died within 30–58 months of therapy, all with systolic HF and a LVEF <30%. In this study, only a small minority of ASV patients fell in the risk group. The number of fatalities did not exceed the expected mortality in optimally treated systolic HF patients. The majority of ASV patients do not fulfil the risk criteria. Fatalities under ASV did not exceed expected figures. http://ow.ly/V2HI30fBURh